NEYRON TARMOG’I YORDAMIDA IRIS O’SIMLIKLARINI TASNIFLASH UCHUN MATLAB DASTURI IMKONIYATLARIDAN FOYDALANISH - Jalelov, R.M. (SCIENCE and SOCIETY, 2021)
This article discusses the problem of classifing iris plants, which is one of the main problem of data mining, and the use of Matlab software to solve it.